Latent transition analysis in organizational psychology: A simplified “how to” guide by using an applied example - Zyberaj, Jetmir; Bakaç, Cafer; Seibel, Sebastian (Frontiers in Psychology, 2022)
With calls for more robust designs in organizational research, there has been a steady increase in the number of longitudinal studies in organizational psychology (OP) journals. Similarly, the number and ways to analyze the longitudinal data have also increased. In this paper, we adopt a relatively new and promising approach that researchers can utilize to analyze their longitudinal data in OP, namely the latent transition analysis (LTA). We present a simplified guideline on LTA and discuss its role for OP researchers. Moreover, we demonstrate how organizational scholars can use this method with a practical example. In this example, we investigate (a) if there are qualitatively distinct subgroups of employees based on particular patterns of psychological capital (PsyCap) dimensions (i.e., efficacy, hope, resilience, and optimism), (b) if employees stay in these subgroups or transition to other groups over time, and finally, (c) if leader-member exchange (LMX) is associated with this transition. We use LTA to examine these steps in a German sample (N = 180).